2013
DOI: 10.1371/journal.pone.0055244
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Subunits in the Adult Rat Hippocampus Undergo Similar Changes after 5 Minutes in an Open Field and after LTP Induction

Abstract: NMDA receptor subunits change during development and their synaptic expression is modified rapidly after synaptic plasticity induction in hippocampal slices. However, there is scarce information on subunits expression after synaptic plasticity induction or memory acquisition, particularly in adults. GluN1, GluN2A and GluN2B NMDA receptor subunits were assessed by western blot in 1) adult rats that had explored an open field (OF) for 5 minutes, a time sufficient to induce habituation, 2) mature rat hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 63 publications
7
32
0
Order By: Relevance
“…Since the ratio between GluN2A and GluN2B subunits is known to change during the course of early brain development and to have a major influence on behavioral and electrophysiological outcomes by adulthood (Traynelis et al, 2010), the shifts we have reported in these two subunits may be among the more important factors in generating the functional synaptic changes described above. As noted earlier, the reduced LTP and GluN2A expression seen here is entirely compatible with the recently reported increase in expression of GluN2A induced by LTP (Baez et al, 2013).…”
Section: Protein and Mrna Expressionsupporting
confidence: 93%
“…Since the ratio between GluN2A and GluN2B subunits is known to change during the course of early brain development and to have a major influence on behavioral and electrophysiological outcomes by adulthood (Traynelis et al, 2010), the shifts we have reported in these two subunits may be among the more important factors in generating the functional synaptic changes described above. As noted earlier, the reduced LTP and GluN2A expression seen here is entirely compatible with the recently reported increase in expression of GluN2A induced by LTP (Baez et al, 2013).…”
Section: Protein and Mrna Expressionsupporting
confidence: 93%
“…3). This led us to the idea that the regulation of the receptor was not at the protein expression level as seen in other memory models (Baez et al 2013) but rather at the surface expression level. The regulation at the surface expression level has been repeatedly reported in memory and synaptic plasticity experiments (Cammarota et al 2000;Grosshans et al 2002b;Moyano et al 2004;Mukherjee et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, this rise would take place during early memory consolidation phase and likely, during the establishment of an “effective” long-term synaptic plasticity (Baez et al, 2013). …”
Section: Introductionmentioning
confidence: 99%